Bioactivities of Dietary Polyphenols and Their Effects on Intestinal Microbiota - Zhang, Xiaoping; Shao, Junjing; Cui, Qinghua; Ni, Wenting; Yang, Ying; Yan, Beibei (Mini Reviews in Medicinal Chemistry, 2023)
The human gut is a complex but stable micro-ecosystem in which the intestinal microbiota play a key role in human health, the health of the intestine and also affect the ability of the host to metabolize nutrients. Intestinal microbiota can affect human physiological functions by regulating host metabolism, immunity and intestinal barrier function. Dysbiosis in the intestinal microbiota is a crucial stimulus for the development of various diseases, which is associated with a variety of diseases in the body. The composition and function of intestinal microbiota depend on the host’s physiological status, genetic makeup, dietary habits, age, and environment, which are the risk factors for obesity, diabetes, cardiovascular diseases and tumors. Polyphenols are important plant secondary metabolites with many physiological functions like anti-oxidation, antitumor, bacteriostasis, cardiovascular and cerebrovascular prevention, and protection of liver and kidney and so on. A large number of studies have confirmed the benefits of dietary polyphenols to human health. Polyphenols and their associated metabolites affect intestinal health and the balance of intestinal microbiota by stimulating the growth of beneficial bacteria and inhibiting the proliferation of pathogens. This review aims to update the current knowledge and highlight how the bioactivities of polyphenols can modulate the intestinal microbiota and regulate the mechanisms of the microbiota, providing a theoretical basis and reference for the scientific and overall use of polyphenols to prevent and treat intestinal diseases and maintain human intestinal health.
Keywords: bioactivity